Quick Cleaning Process for Silicon Carbide Chemical Vapor Deposition Reactor. (7th July 2017) - Shioda, Kohei; Kurashima, Keisuke; Habuka, Hitoshi; Ito, Hideki; Mitani, Shin-ichi; Takahashi, Yoshinao
Abstract : A quick cleaning process was developed for a silicon carbide chemical vapor deposition reactor. For this purpose, the stability of the susceptor coating film made of pyrolytic carbon was evaluated by means of exposing it to 100% chlorine trifluoride gas for 10 min at various temperatures. The original surface morphology of the pyrolytic carbon film was maintained under 480°C. The fluorine atoms incorporated into the pyrolytic carbon film were removed by annealing at 900°C either in ambient hydrogen or in ambient nitrogen. Finally, the 30-μm thick silicon carbide film formed on the pyrolytic carbon was successfully cleaned by the chlorine trifluoride gas either at 400°C for 30 min or at 460°C for 15 min and by additional annealing in ambient nitrogen at 900°C.